Demineralization of cocoons of Antheraea assamensis Helfer (muga) for effective reeling. Issue 4 (3rd April 2018) - Choudhury, Manasee; Devi, Dipali
Abstract: Muga cocoons are evidenced of possessing heavy deposition of minerals (such as calcium oxalate) on its surface. This mineral deposition restricts reeling of muga fiber in comparison to the cocoons of mulberry silkworm. In this study, we have attempted to wash out the mineral layer using various chemical and natural agents like ethylenediaminetetraacetic acid (EDTA), potassium carbonate, citric acid, extract of Musa balbisiana ('kolakhar'), and Citrus limon (lemon), respectively. It is observed that both the natural and chemical agents carefully removes the mineral deposition, leaving the gummy sericin substantially intact, preventing entanglement of fibroin brins, and permitting wet reeling with very minimum number of fiber breaks compared to commercial degumming. The removal of granular minerals was evidenced by surface morphology and FTIR spectroscopy of demineralized cocoon fiber. Further, the tensile strength of demineralized fiber showed superiority in contrast to sodium carbonate degummed fiber. Under the implemented experimental conditions 'kolakhar' functioned as the most efficient demineralizing agent amongst all. Therefore, the present study demonstrates an improved method for softening wild silk cocoons in contrast to harsh degumming for obtaining long continuous reeled fiber threads with very less number of fiber breaks and enhanced mechanical strength.